Negative electrode material and preparation method thereof, negative electrode plate and secondary battery

By coating the surface of graphite anode material with a nitrogen-doped carbon layer and a metal oxide layer, the problems of poor fast-charging performance and electrolyte compatibility of graphite anode material are solved, achieving efficient lithium-ion transport and structural stability, and improving the electrochemical performance and lifespan of the battery.

CN120895633APending Publication Date: 2025-11-04REPT BATTERO ENERGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511086924.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-04
Publication Date
2025-11-04

AI Technical Summary

Technical Problem

Existing graphite anode materials suffer from poor fast-charging performance and poor compatibility with electrolytes during charging and discharging, leading to electrode structure collapse and decreased electrochemical performance.

Method used

The structure adopts a graphite core and a nitrogen-doped carbon layer and a metal oxide layer as the coating. The nitrogen-doped carbon layer contains metal phosphide particles, which reduce the interfacial impedance through CP chemical bonding. The metal oxide layer stabilizes the interface and blocks solvent molecule contact, forming a dual physical-chemical protection.

Benefits of technology

It improves the lithium-ion diffusion rate and initial charge/discharge efficiency, mitigates structural damage caused by volume changes during cycling and electrolyte compatibility, and extends electrode lifespan and battery power performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120895633A_ABST
    Figure CN120895633A_ABST
Patent Text Reader

Abstract

The invention provides a negative electrode material and a preparation method thereof, a negative electrode plate and a secondary battery. The negative electrode material comprises an inner core and a coating layer, the inner core is made of graphite, the coating layer comprises a nitrogen-doped carbon layer and a metal oxide layer which are arranged from inside to outside, and the nitrogen-doped carbon layer contains metal phosphide particles. The coating layer of the negative electrode material comprises the nitrogen-doped carbon layer and the metal oxide layer which are arranged from inside to outside, and due to the existence of the coating layer, compared with a common graphite negative electrode material, the negative electrode material disclosed by the invention has relatively high lithium ion diffusion rate and first charge-discharge efficiency; and the problems of structural damage caused by large volume change in the circulation process and poor compatibility with electrolyte can be effectively improved, and the power and the service life can be remarkably improved when the material is applied to a battery.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of batteries, in particular to a negative electrode material, a preparation method thereof, a negative electrode sheet and a secondary battery. BACKGROUND

[0002] Lithium ion batteries, as a kind of energy storage devices with high energy density, good cycle performance and long service life, are widely used in many fields such as new energy vehicles, power tools and consumer electronics. With the rapid development of new energy vehicles and the continuous growth of power tools and consumer electronics, the demand for lithium ion batteries is increasing.

[0003] Graphite material, as one of the commonly used negative electrode materials for lithium ion batteries, has the advantages of large theoretical capacity, stable structure, low cost and abundant resources. However, during the charging and discharging process, the graphite material will expand in volume, causing the electrode material to fall off from the current collector, resulting in the collapse of the electrode structure and affecting the electrochemical performance of the electrode. Therefore, a carbon layer with good electrical conductivity needs to be coated on the surface of the graphite material to improve the electrical conductivity of the graphite material and prevent the volume expansion of the graphite material, thereby prolonging the service life of the electrode. However, most of the carbon layer materials on the market have poor electrochemical performance due to their own defects, which cannot meet the needs of practical applications. SUMMARY

[0004] The main purpose of the present application is to provide a negative electrode material, a preparation method thereof, a negative electrode sheet and a secondary battery, to solve the problems of poor fast charging performance and poor compatibility with electrolyte of the graphite negative electrode material in the prior art.

[0005] In order to achieve the above-mentioned purpose, according to one aspect of the present application, a negative electrode material is provided, which comprises: an inner core and a coating layer, the material of the inner core is graphite, the coating layer comprises a nitrogen-doped carbon layer and a metal oxide layer arranged from inside to outside, and the nitrogen-doped carbon layer contains metal phosphide particles.

[0006] Further, the thickness of the nitrogen-doped carbon layer is 20-40 nm;

[0007] The carbon in the nitrogen-doped carbon layer is amorphous carbon;

[0008] The mass content of nitrogen element in the negative electrode material is 3-6%;

[0009] Further, the average particle size of the metal phosphide particles is 6-10 nm;

[0010] The metal phosphide includes any one or more of FeP, MnP, NiP and CoP;

[0011] The mass fraction of the metal phosphide particles in the negative electrode material is 0.5-2%.

[0012] Further, the material of the metal oxide layer is aluminum oxide;

[0013] The thickness of the metal oxide layer is 0.5-1.5 nm;

[0014] The particle size D50 of the core is 10.08-15.1 μm.

[0015] Further, the particle size D50 of the negative electrode material is 10.5-15.5 μm;

[0016] The electrical conductivity of the negative electrode material is 4.75-9.85 S / cm;

[0017] The specific surface area of the negative electrode material is 1.0-1.6 m 2 / g.

[0018] According to another aspect of the present application, a preparation method of a negative electrode material is provided, comprising: mixing graphite, Tris buffer and a carbon source, removing the liquid phase components to obtain a first precursor, the carbon source being an amine polymer; mixing the first precursor with a phosphorus source solution to obtain a second precursor, and performing sintering treatment on the second precursor to obtain a third precursor; depositing a metal oxide layer on the surface of the third precursor to obtain the negative electrode material.

[0019] Further, the graphite is activated graphite, and the surface of the activated graphite contains any one or more of sulfonic acid groups and phosphoric acid groups;

[0020] The step of preparing the activated graphite comprises: mixing graphite raw material with an activation treatment solution, ultrasonic treatment, washing, and drying to obtain the activated graphite; the activation treatment solution is a concentrated acid and a hydrogen peroxide solution in a volume ratio of 2:1-4:1;

[0021] Preferably, the concentrated acid is concentrated sulfuric acid and / or concentrated phosphoric acid;

[0022] Preferably, the temperature of the ultrasonic treatment is 50-70°C;

[0023] Preferably, the time of the ultrasonic treatment is 1-3 h.

[0024] Further, the mass ratio of the graphite to the carbon source is 1:(0.2-0.4);

[0025] The carbon source is selected from any one or more of polydopamine, polyethyleneimine, polyaniline, polyimide, dicyandiamide, and melamine resin;

[0026] The weight average molecular weight of the carbon source is 60000-80000 Da;

[0027] The pH value of the Tris buffer is 8-9;

[0028] The phosphorus source includes any one or more of NH4FePO4, NH4CoPO4·H2O, NH4MnPO4 and (NH4)2NiPO4;

[0029] The concentration of the phosphorus source solution is 0.3-0.7 mol / L;

[0030] The sintering treatment is performed at a temperature of 700-900 DEG C for 2-6 hours.

[0031] The step of depositing a metal oxide layer on the surface of the third precursor includes: forming the metal oxide layer by outer atomic layer deposition of the third precursor; preferably, the temperature of the outer atomic layer deposition is 70-90 DEG C; preferably, the number of cycles of the outer atomic layer deposition is 5-10.

[0032] According to yet another aspect of the present application, a negative electrode sheet is provided, the negative electrode material containing any one of the negative electrode materials or the negative electrode material prepared by any one of the preparation methods.

[0033] According to still another aspect of the present application, a secondary battery is provided, including the negative electrode sheet.

[0034] By applying the technical scheme of the present application, the negative electrode material includes an inner core and a coating layer, the material of the inner core is graphite, the coating layer includes a nitrogen-doped carbon layer and a metal oxide layer arranged from inside to outside, the nitrogen-doped carbon layer contains metal phosphide particles, the nitrogen-doped carbon layer can provide an electron fast transmission channel, the metal phosphide therein acts as a "lithium ion pump" and can accelerate the desolvation of Li + ; the nitrogen-doped carbon material in the nitrogen-doped carbon layer can be chemically bonded with the metal phosphide through a C-P bond, reducing the interface impedance, the metal oxide in the outer layer is relatively stable in nature, inhibiting the generation of organic SEI, the metal oxide layer can block the direct contact of solvent molecules with graphite, reducing the organic products such as RCO2Li, improving the initial efficiency, thereby achieving physical-chemical dual protection of the internal material. Due to the presence of the coating layer, the negative electrode material of the present application has a higher lithium ion diffusion rate and initial charge-discharge efficiency compared with ordinary graphite negative electrode materials, and can effectively improve the problems of large volume change leading to structural damage and poor compatibility with electrolyte during the cycle process, and can significantly improve the power and service life when applied in a battery. BRIEF DESCRIPTION OF DRAWINGS

[0035] The drawings accompanying the specification of the present application form a part thereof, serve to provide further understanding of the present application, and together with the specification explain the application, and do not limit the present application. In the drawings:

[0036] Figure 1A field emission scanning electron microscope (FE-SEM) image of the negative electrode material prepared according to Embodiment 1 of the present application is shown;

[0037] Figure 2 An EDS element mapping energy spectrum picture of the negative electrode material prepared according to Embodiment 1 of the present application is shown;

[0038] Figure 3 A high-resolution transmission electron microscope (HR-TEM) image of the negative electrode material prepared according to Embodiment 1 of the present application is shown. DETAILED DESCRIPTION

[0039] It should be noted that the embodiments in the present application and the features in the embodiments can be combined with each other without conflict. The present application will be described in detail below with reference to the accompanying drawings and in combination with embodiments.

[0040] As analyzed in the background art of the present application, there are problems of poor fast-charging performance and poor compatibility with electrolyte in the prior art graphite negative electrode material. In order to solve the problem, the present application provides a negative electrode material, a preparation method thereof, a negative electrode sheet and a secondary battery.

[0041] According to a typical embodiment of the present application, a negative electrode material is provided, which comprises: an inner core and a coating layer, the material of the inner core is graphite, the coating layer comprises a nitrogen-doped carbon layer and a metal oxide layer arranged from inside to outside, and the nitrogen-doped carbon layer contains metal phosphide particles.

[0042] The negative electrode material of the present application comprises an inner core and a coating layer, the material of the inner core is graphite, the coating layer comprises a nitrogen-doped carbon layer and a metal oxide layer arranged from inside to outside, and the nitrogen-doped carbon layer contains metal phosphide particles, wherein the nitrogen-doped carbon layer can provide an electron fast transmission channel, and the metal phosphide therein acts as a "lithium ion pump" to accelerate Li + desolvation; and the nitrogen-doped carbon material in the nitrogen-doped carbon layer and the metal phosphide can be chemically bonded through a C-P bond to reduce the interface impedance, the metal oxide in the outer layer is relatively stable in nature, inhibits the generation of organic SEI, and the metal oxide layer can block the direct contact of solvent molecules with graphite, reduce organic products such as ROCO2Li, and improve the initial efficiency, thereby achieving physical-chemical dual protection of the internal material. Due to the presence of the above-mentioned coating layer, the negative electrode material of the present application has a higher lithium ion diffusion rate and a higher first charge-discharge efficiency compared with ordinary graphite negative electrode materials, and can effectively improve the problems of large volume change leading to structural damage and poor compatibility with electrolyte during the cycle process, and can significantly improve the power and service life when applied in a battery.

[0043] The nitrogen-doped carbon layer in the fast-charging graphite negative electrode mainly improves the electrochemical performance of the negative electrode material through nitrogen element-induced electronic structure regulation and surface chemical modification. The mechanism is as follows: first, electronic structure regulation: nitrogen can replace the Sp2 hybridization of carbon atoms, introduce free electrons, make the carbon Fermi level move up, significantly improve the electrical conductivity, and build a hole conduction network to promote the rapid transfer of electrons to the current collector during charging and discharging; second, surface chemical modification: nitrogen atom (N atom radius 70 pm vs. C atom radius 77 pm) doping leads to carbon lattice distortion, generating topological defects. The defect sites act as lithium ion adsorption sites, and the adsorption energy is increased to -2.8 eV (un-doped carbon: -1.5 eV), enhancing the Li + interface capture ability, optimizing the transmission of lithium ions; third, interface stability enhancement: nitrogen-containing groups induce the generation of Li3N-rich SEI films, and the Li3N ion conductivity is as high as 10-3 S / cm, which improves the migration rate of Li + in the SEI, inhibits dendrite growth; fourth, synergistic effect: in the gradient heterojunction design, the nitrogen-doped carbon layer is coupled with the metal phosphide through the C-P bond, reducing the interface impedance, and the nitrogen-doped carbon layer fixes the metal phosphide particles, preventing the metal phosphide particles from falling off due to graphite expansion during the cycle process, and maintaining a high retention rate after cycling.

[0044] In some embodiments of the present application, the thickness of the above-mentioned nitrogen-doped carbon layer is 20-40 nm. Within the above thickness range, the nitrogen-doped carbon layer not only effectively provides a fast electron transmission channel, but also ensures that the diffusion path of lithium ions between the graphite layers will not be lengthened due to excessive coating, while providing enough space for lithium ion intercalation and deintercalation, accelerating the migration speed of lithium ions, better optimizing the transmission of lithium ions, especially under fast charging conditions, reducing the polarization effect of lithium ions, and preventing lithium precipitation. In addition, the nitrogen-doped carbon layer with the above thickness can effectively isolate the direct contact between graphite and electrolyte, reduce the volume expansion problem of graphite during charging and discharging, thereby enhancing the mechanical stability of the electrode, reducing the loss of active material during the cycle process, and improving the cycle life. Specifically, the thickness of the nitrogen-doped carbon layer can be 20 nm, 22 nm, 25 nm, 28 nm, 30 nm, 32 nm, 35 nm, 38 nm, 40 nm, or any other value within the above range, which is not limited herein.

[0045] In some embodiments of the present application, the carbon in the carbon-doped layer is amorphous carbon, which has no clear lattice direction and provides more flexible embedding paths for lithium ions, reducing the diffusion barrier of lithium ions during charging and discharging, thereby improving the rate performance of lithium ion batteries. After the amorphous carbon is doped with nitrogen elements, more conductive sites can be formed due to the electron transfer between nitrogen atoms and carbon atoms, increasing the electron transport path and effectively improving the electronic conductivity of the material and the electrochemical reaction kinetics of the battery. In addition, compared with crystalline carbon, the volume change of amorphous carbon structure during lithium ion intercalation and deintercalation is smaller, which helps to maintain the structural stability of the electrode material, reduce the pulverization and shedding during the cycle process, and improve the cycle stability and life of the battery. The irregularity of the amorphous carbon structure makes it easier for nitrogen atoms to be uniformly distributed in the carbon layer, thereby optimizing the adsorption and desorption behavior of lithium ions and comprehensively improving the conductivity, structural stability and compatibility with electrolyte of the graphite negative electrode material.

[0046] In some embodiments of the present application, the mass content of nitrogen elements in the negative electrode material is 3-6%, which can be 3%, 3.5%, 4%, 4.5%, 5%, 5.5%, 6% or any other value within the above range, which is not limited herein. Controlling the content of nitrogen elements in the nitrogen-doped amorphous carbon layer (N-C layer) within the above range is beneficial to obtain a comprehensive optimization result based on electronic transmission, structural stability and interface kinetics, and better achieve the balance of electronic conduction, ion diffusion and structural stability. When the content of nitrogen elements is too low, it is difficult to form a continuous electronic channel, and the formed Li + defect adsorption sites are reduced. When the content of nitrogen elements is too high, sp 2 C-N bonds in the carbon skeleton are too high, the mechanical strength is reduced, and in addition, nitrogen can induce the formation of Li-rich SEI film, and excessive nitrogen can excessively consume Li + in the electrolyte, resulting in the formation of a too thick SEI.

[0047] The above metal phosphide can significantly reduce the interface impedance. Taking FeP as an example, the mechanism of its action is as follows: ① "Lithium ion pump" accelerates desolvation: P atoms in FeP have strong lithium affinity, which combines with solvated lithium ions (such as Li + (EC)4) in the electrolyte, weakens the Li + -solvent bond energy, and reduces the desolvation energy barrier from 0.8 eV of traditional graphite to 0.5 eV, thereby improving the Li + migration rate. ② Ion diffusion channel: FeP nanoparticles provide a short-range ion diffusion path, and the lithium ion diffusion coefficient is improved. ③ Conversion reaction buffer volume expansion: during the charging and discharging process, the reversible reaction: The high ionic conductivity of Li3P maintains the interface ion transmission efficiency. ④ Provides an electron-ion double continuous transmission network: electrons are conducted to the FeP interface through the N-C layer, and ions are injected into the graphite layer through FeP, solving the problem of mismatch between traditional graphite electron / ion transmission. ⑤ SEI film synergistic regulation: N-C layer induces the generation of Li3N, reduces SEI impedance, FeP preferentially converts the reaction to consume active lithium, reduces electrolyte decomposition, and inhibits the growth of organic SEI.

[0048] In some embodiments of the present application, the metal phosphide includes any one or more of FeP, MnP, NiP, CoP, which has a good effect as a "lithium ion pump", and can further increase the Li + desolvation rate and reduce interface impedance.

[0049] In some embodiments of the present application, the average particle size of the metal phosphide particles is 6-10 nm, which can more effectively act as a "lithium ion pump" to accelerate the Li + desolvation. Specifically, the average particle size of the metal phosphide particles can be 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, or other values within the above range. The average particle size of the metal phosphide particles can be obtained by transmission electron microscopy test.

[0050] In some embodiments of the present application, the mass fraction of the metal phosphide particles in the negative electrode material is 0.5-2%, and can be 0.5%, 0.8%, 1%, 1.2%, 1.5%, 1.8%, 2%, etc., which is not limited herein.

[0051] In some embodiments of the present application, the material of the metal oxide layer is aluminum oxide; the presence of the metal oxide layer with aluminum oxide material effectively prevents the direct contact of the electrolyte with the negative electrode material, reducing the occurrence of side reactions. In particular, when the material of the metal oxide layer is aluminum oxide, the effect of improving the structural stability of the negative electrode material is particularly significant, and the preparation process is easy to control.

[0052] In some embodiments of the present application, the thickness of the metal oxide layer is 0.5-1.5 nm, which can improve the structural stability of the negative electrode material while providing a good lithium ion transmission channel, thereby improving the safety and cycle life of the battery. Specifically, the thickness of the metal oxide layer can be 0.5 nm, 0.8 nm, 1 nm, 1.2 nm, 1.5 nm, etc., or other values within the above range.

[0053] In some embodiments of the present application, the particle size D50 of the core is 10.08-15.1 μm. Specifically, it can be 10.08 μm, 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 14.5 μm, 15 μm, 15.1 μm, etc., which are not limited herein.

[0054] In some embodiments of the present application, the particle size D50 of the negative electrode material is 10.5-15.5 μm. Specifically, it can be 10.5 μm, 11 μm, 11.5 μm, 12 μm, 12.5 μm, 13 μm, 13.5 μm, 14 μm, 14.5 μm, 15 μm, 15.5 μm, etc., which are not limited herein.

[0055] In some embodiments of the present application, the electrical conductivity of the negative electrode material is 4.75-9.85 S / cm. Specifically, it can be 4.75 S / cm, 5 S / cm, 5.5 S / cm, 6 S / cm, 6.5 S / cm, 7 S / cm, 7.5 S / cm, 8 S / cm, 8.5 S / cm, 9 S / cm, 9.5 S / cm, 9.85 S / cm, etc., which are not limited herein.

[0056] In some embodiments of the present application, the specific surface area of the negative electrode material is 1.0-1.6 m 2 / g. Specifically, it can be 1.0 m 2 / g, 1.1 m 2 / g, 1.2 m 2 / g, 1.3 m 2 / g, 1.4 m 2 / g, 1.5 m 2 / g, 1.6 m 2 / g, etc., or other values within the above range.

[0057] According to another typical embodiment of the present application, a preparation method of a negative electrode material is provided, which comprises: mixing graphite, Tris buffer and carbon source, removing the liquid phase components to obtain a first precursor; wherein the carbon source is an amine polymer; mixing the first precursor with a phosphorus source solution to obtain a second precursor, and performing sintering treatment on the second precursor to obtain a third precursor; depositing a metal oxide layer on the surface of the third precursor to obtain the negative electrode material.

[0058] The preparation method above uses an amine-containing amine polymer as a carbon source, and can provide nitrogen elements in the nitrogen-doped carbon layer. In the sintering process, the carbon source and the phosphorus source are converted in situ, and a nitrogen-doped carbon coating layer and metal phosphide particles in the nitrogen-doped carbon layer are formed. The metal phosphide particles are uniformly distributed in the nitrogen-doped carbon layer, and the process steps are simplified. Further, by arranging the metal oxide layer, the prepared negative electrode material has a coating layer including the nitrogen-doped carbon layer and the metal oxide layer arranged from inside to outside. The nitrogen-doped carbon layer can provide an electron fast transmission channel, and the metal phosphide therein can act as a "lithium ion pump" to accelerate Li + desolvation; and the nitrogen-doped carbon material in the nitrogen-doped carbon layer and the metal phosphide can be chemically bonded through a C-P bond to reduce the interface impedance. The metal oxide in the outer layer has stable properties and can achieve physical-chemical double protection for the internal material. Therefore, the negative electrode material has significant advantages in terms of first charge-discharge efficiency, reversible specific capacity, rate performance, and cycle stability, and the electrochemical performance is significantly improved.

[0059] In some embodiments of the present application, the graphite is activated graphite, and the surface of the activated graphite contains any one or more of sulfonic acid groups and phosphoric acid groups. The activated groups on the surface of the activated graphite can form chemical bonds with the carbon source to enhance the bonding force between the nitrogen-doped coating layer and the graphite core and prevent the coating layer from falling off. For example, when the carbon source is polydopamine, the ortho-benzene diol groups form covalent bonds, which can significantly increase the bonding force between the nitrogen-doped coating layer and the graphite core.

[0060] In some embodiments of the present application, the step of preparing the activated graphite includes mixing the graphite raw material with an activation treatment solution, ultrasonic treatment, washing, and drying to obtain the activated graphite. The activated graphite obtained by the above method has a surface rich in -SO3H groups. Preferably, the activation treatment solution is a concentrated acid and a hydrogen peroxide solution in a volume ratio of 2:1 to 4:1. Preferably, the concentrated acid is concentrated sulfuric acid and / or concentrated phosphoric acid. The mass concentration of the concentrated sulfuric acid is 70-98%, the mass concentration of the concentrated phosphoric acid is 85-89%, and the mass concentration of the hydrogen peroxide solution is 20-40%. Preferably, the ultrasonic treatment is performed at a temperature of 50-70°C for 1-3 hours.

[0061] The graphite raw material described above can be selected from the prior art. For example, the graphite raw material can be any one or more of artificial graphite and natural graphite. Preferably, the graphite raw material has needle-shaped coke as the graphite coke source, and the mass ratio of primary particles to secondary particles is (2-4):(6-8), the particle size D50 is 12-15 μm, the first efficiency is >85.0%, and the gram capacity is >330 mAh / g.

[0062] In some embodiments of the present application, the mass ratio of graphite to carbon source is 1:(0.2-0.4), which is helpful to form a nitrogen-doped carbon layer with a proper thickness.

[0063] In some embodiments of the present application, the carbon source is selected from any one or more of polydopamine, polyethyleneimine, polyaniline, polyimide, dicyandiamide, and melamine resin.

[0064] In some embodiments of the present application, the weight average molecular weight of the carbon source is 60000-80000 Da.

[0065] The main component of Tris buffer is tris(hydroxymethyl)aminomethane (Tris, chemical formula C4H 11 NO3), the chemical name of which is 2-(trishydroxymethyl)aminoethanol. In some embodiments of the present application, the pH value of the Tris buffer is 8-9; using the Tris buffer with the above pH range is helpful to provide an environment suitable for self-assembly of the carbon source. Taking polydopamine as an example, polydopamine is similar to dopamine in the body and can spontaneously polymerize on the surface of a material to form a thin film under alkaline conditions. By adjusting the pH value of the Tris buffer, the polymerization rate and properties of the carbon source can be controlled, thereby affecting the formation characteristics of the subsequent nitrogen-doped carbon layer, so that the prepared negative electrode material has more comprehensive performance.

[0066] In some embodiments of the present application, the step of mixing graphite, Tris buffer and carbon source, and removing the liquid phase component to obtain a first precursor includes: dispersing the above-mentioned activated graphite in the Tris buffer, adding the carbon source, stirring at 20-35°C for 10-15 h, centrifuging and drying to obtain a first precursor with a uniform carbon source coating layer.

[0067] Mixing the above-mentioned first precursor with a phosphorus source solution and then performing sintering treatment can make the generated metal phosphide more uniformly distributed in the nitrogen-doped carbon layer, and the carbonization of the carbon source and the generation of the metal phosphide are completed synchronously, which not only can reduce the process steps, but also is helpful to promote the chemical bonding between the nitrogen-doped carbon material in the nitrogen-doped carbon layer and the metal phosphide through C-P bonds, thereby reducing the interface impedance.

[0068] In some embodiments of the present application, the above-mentioned phosphorus source can provide metal cations and phosphate ions (PO43-), and can be decomposed to generate the target metal phosphide during the sintering process. In some embodiments thereof, the phosphorus source includes any one or more of NH4FePO4, NH4CoPO4·H2O, NH4MnPO4, and (NH4)2NiPO4.

[0069] In some embodiments of the present application, the concentration of the phosphorus source solution is 0.3-0.7 mol / L.

[0070] In some embodiments of the present application, the step of mixing the first precursor with the phosphorus source solution to obtain the second precursor comprises: immersing the first precursor in the phosphorus source solution, standing for 2-6 hours in a vacuum environment, and then performing a drying treatment to obtain the second precursor. The surface of the activated graphite has a large number of micropores (pore size 2-5 nm) and mesopores (pore size 10-50 nm). Under normal pressure, the solution cannot completely fill the pores due to air resistance. Under vacuum, the gas in the pores is removed, so that the phosphorus source solution penetrates into the pores under the driving of negative pressure, thereby increasing the bonding strength of the formed coating layer and the graphite core and improving the electrochemical performance thereof. Preferably, the drying treatment comprises stirring the material after standing at a speed of 400-800 rpm / min at 40-60°C until the solvent of the phosphorus source solution is completely evaporated.

[0071] In some embodiments of the present application, the sintering treatment has a temperature of 700-900°C and a time of 2-6 hours. In some embodiments of the present application, the sintering treatment is performed in a mixed atmosphere of a protective gas and hydrogen, wherein the protective gas comprises any one or more of helium, argon, neon, xenon and nitrogen, and the volume fraction of the hydrogen in the mixed atmosphere is 5-8%.

[0072] In some embodiments of the present application, the step of depositing a metal oxide layer on the surface of the third precursor comprises: forming a metal oxide layer on the surface of the third precursor by atomic layer deposition (ALD); and performing coating of the metal oxide layer by ALD, so that the formed coating layer is relatively uniform and the thickness of the metal oxide layer can be accurately controlled. Preferably, the temperature of the ALD is 70-90°C; and preferably, the number of cycles of the ALD is 5-10.

[0073] According to another typical embodiment of the present application, a negative electrode sheet is provided, which contains any one of the negative electrode materials or the negative electrode material prepared by any one of the preparation methods.

[0074] The above negative electrode material can provide a fast electron transport channel, accelerate the desolvation of Li + , has a high lithium ion diffusion rate and a high first charge-discharge efficiency, and the negative electrode sheet using the same as an active material has excellent electrochemical performance and cycle stability, which can significantly improve the power and service life of the battery.

[0075] According to a typical embodiment of the present application, a secondary battery is provided, which comprises the above negative electrode sheet. Since the above negative electrode sheet is used, the secondary battery of the present application has a better reversible specific capacity, rate performance and cycle stability, and is suitable for fields such as electric vehicles and portable electronic devices with high requirements.

[0076] The beneficial effects that can be achieved by the present application will be further illustrated below in combination with examples and comparative examples.

[0077] Example 1

[0078] (1) Graphite pretreatment: 10 g of artificial graphite raw material (D50 of 12.5 μm, Zhongke Xingcheng Graphite Co., Ltd., brand: RPG215) was selected and mixed with 150 ml of concentrated sulfuric acid (mass concentration of 98%, Shanghai Aldrich Biochemical Technology Co., Ltd., brand: S433910) / 50 ml of hydrogen peroxide (mass concentration of hydrogen peroxide of 30%, Xilong Scientific Co., Ltd., brand: 1560010104299), and was treated by ultrasonic at 60°C for 2 h to obtain activated graphite with a surface rich in sulfonic acid groups (-SO3H), which was washed to neutral with distilled water and then vacuum dried.

[0079] (2) In-situ synthesis of nitrogen-doped carbon / metal phosphide heterojunction: The activated graphite was dispersed in 200 ml of Tris buffer solution (pH = 8.5, Shanghai Aldrich Biochemical Technology Co., Ltd., brand: T755550), 3 g of polydopamine (mass ratio to graphite of 0.3:1, weight average molecular weight of 70000 Da, Shanghai Aldrich Biochemical Technology Co., Ltd., brand: D103111) was added, and stirring was carried out at room temperature for 12 h, followed by centrifugal drying to form a first precursor with a uniform polydopamine coating layer. The dried material was immersed in 20 mL of 0.5 mol / L NH4FePO4 solution (Shanghai Aldrich Biochemical Technology Co., Ltd., brand: F188971), and was allowed to stand in a vacuum environment for 4 h to form a second precursor. Then, stirring was carried out at 50°C at 600 rpm / min until the solvent of the NH4FePO4 solution was completely evaporated, and the third precursor was obtained by grinding and crushing under an Ar / H2 (95% / 5%) atmosphere and annealing at 800°C for 4 h.

[0080] (3) Al2O3 coating treatment: The third precursor material was transferred to an ALD reaction cavity, the temperature was set to 80°C, the cycle parameters were set to TMA pulse of 0.1 s, nitrogen blowing for 10 s, H2O pulse of 0.05 s, and nitrogen blowing for 10 s. Six cycles of deposition were carried out to obtain an Al2O3 layer with a thickness of 1 nm. Thus, a negative electrode material with a nitrogen-doped carbon / metal phosphide / oxide gradient heterojunction interface layer was prepared.

[0081] Figure 1 The field emission scanning electron microscope image of the negative electrode material prepared in this example can be seen from Figure 1 which shows the blocky morphology of the graphite.

[0082] Figure 2The EDS element mapping spectrum picture of the negative electrode material prepared in the embodiment. In the EDS element mapping spectrum, N, C, Fe, P, O and Al elements are uniformly distributed, indicating that the nitrogen-doped carbon layer, the FeP layer and the Al2O3 coating are successfully formed on the surface of the graphite.

[0083] Figure 3 The high-resolution transmission electron microscope (HR-TEM) image of the negative electrode material prepared in the embodiment. The HR-TEM image shows that the lattice fringe spacing in the upper left part is 0.3354 nm, corresponding to the (002) crystal plane of the graphite crystal, and the lower right part presents an amorphous carbon component, proving the existence of the carbon layer.

[0084] Example 2

[0085] (1) Graphite pretreatment: 8 g of artificial graphite raw material (D50 is 10.08 μm, Zhongke Xingcheng Graphite Co., Ltd., brand: RPG215) was selected and mixed with 120 ml of concentrated sulfuric acid (mass concentration is 98%, Shanghai Aldrich Biochemical Technology Co., Ltd., brand: S433910) and 60 ml of hydrogen peroxide (mass concentration of hydrogen peroxide is 30%, Xilong Scientific Co., Ltd., brand: 1560010104299), and was treated by ultrasonic at 50°C for 3 h to obtain activated graphite with a surface rich in sulfonic acid groups (-SO3H). After washing to neutral with distilled water, vacuum drying was performed.

[0086] (2) In-situ synthesis of nitrogen-doped carbon / metal phosphide heterojunction: The activated graphite was dispersed in 1500 ml of Tris buffer solution (pH = 8, Shanghai Aldrich Biochemical Technology Co., Ltd., brand: T755550), 1.6 g of polyethyleneimine (mass ratio to graphite is 0.2:1, weight average molecular weight is 60000 Da, Shanghai Aldrich Biochemical Technology Co., Ltd., brand: E107077) was added, and stirring was performed at room temperature for 12 h, centrifugal drying was performed, and the first precursor with a uniform polyethyleneimine coating layer was formed. The dried material was immersed in 20 mL of 0.3 mol / L NH4CoPO4 solution (Shanghai Aldrich Biochemical Technology Co., Ltd., brand: F486794), and was placed in a vacuum environment for 4 h to form the second precursor. Then, stirring was performed at 600 rpm / min at 50°C until the solvent of the NH4CoPO4 solution was completely evaporated, and the third precursor was formed after grinding and crushing in an Ar / H2 (95% / 5%) atmosphere at 700°C for 6 h.

[0087] (3) Al2O3coating treatment: transfer the material to the ALD reaction cavity, set the temperature to 70°C; the cycle parameters are set as TMA pulse 0.1 s, nitrogen blowing 10 s, H2O pulse 0.05 s, nitrogen blowing 10 s. Deposit 10 cycles to obtain an Al2O3 layer with a thickness of 0.5 nm. The negative electrode material of the nitrogen-doped carbon / metal phosphide / oxide gradient heterojunction interface layer is prepared.

[0088] Example 3

[0089] (1) Graphite pretreatment: select 10 g of artificial graphite raw material (D50 is 15.1 μm, Zhongke Xingcheng Graphite Co., Ltd., brand: RPG215), mix with 160 ml of concentrated phosphoric acid (mass concentration is 98%, Shanghai Aladdin Bio-Chem Technology Co., Ltd., brand: S433910) / 40 ml of hydrogen peroxide (mass concentration of hydrogen peroxide is 30%, Xilong Scientific Co., Ltd., brand: 1560010104299), ultrasonic treatment at 70°C water bath for 1 h, obtain activated graphite with rich sulfonic acid groups (-SO3H) on the surface, and then wash with distilled water until neutral and vacuum dry.

[0090] (2) In-situ synthesis of nitrogen-doped carbon / metal phosphide heterojunction: disperse the activated graphite in 1500 ml of Tris buffer solution (pH = 9, Shanghai Aladdin Bio-Chem Technology Co., Ltd., brand: T755550) and add 4 g of polyimide (mass ratio to graphite is 0.4:1, weight average molecular weight is 80000 Da, Shanghai Aladdin Bio-Chem Technology Co., Ltd., brand: P406634), stir at room temperature for 12 h, centrifugal dry, and form a first precursor with a uniform polyethyleneimine coating layer. Dip the dried material in 20 mL of 0.7 mol / L NH4MnPO4 solution (Shanghai Aladdin Bio-Chem Technology Co., Ltd., brand: M332865), and stand still in a vacuum environment for 4 h to form a second precursor. Then stir at 600 rpm / min at 50°C until the solvent of the NH4MnPO4 solution is completely evaporated, fully grind and crush, and anneal at 900°C for 2 h in an Ar / H2(95% / 5%) atmosphere to form a third precursor.

[0091] (3) Al2O3coating treatment: transfer the material to the ALD reaction cavity, set the temperature to 90°C; the cycle parameters are set as TMA pulse 0.1 s, nitrogen blowing 10 s, H2O pulse 0.05 s, nitrogen blowing 10 s. Deposit 5 cycles to obtain an Al2O3 layer with a thickness of 1.5 nm. The negative electrode material of the nitrogen-doped carbon / metal phosphide / oxide gradient heterojunction interface layer is prepared.

[0092] Example 4

[0093] The difference from Example 1 is only that in step (2), 1 g of polydopamine is added, and the mass ratio of polydopamine to graphite is 0.1:1.

[0094] Example 5

[0095] The difference from Example 1 is only that in step (2), 5 g of polydopamine is added, and the mass ratio of polydopamine to graphite is 0.5:1.

[0096] Example 6

[0097] The difference from Example 1 is only that in step (2), the concentration of the NH4FePO4 solution is 0.2 mol / L.

[0098] Example 7

[0099] The difference from Example 1 is only that in step (2), the concentration of the NH4FePO4 solution is 0.8 mol / L.

[0100] Comparative Example 1

[0101] The same artificial graphite raw material as in Example 1 is directly used as the negative electrode material.

[0102] Comparative Example 2

[0103] The difference from Example 1 is that step (3) is not performed, and the second precursor prepared in step (2) is used as the negative electrode material.

[0104] Comparative Example 3

[0105] (1) Graphite pretreatment: 10 g of artificial graphite raw material (D50 of 12.5 μm, Zhongke Xingcheng Graphite Co., Ltd., brand: RPG215) is mixed with 150 ml of concentrated sulfuric acid (mass concentration of 98%, Shanghai Aladdin Bio-Chem Technology Co., Ltd., brand: S433910) / 50 ml of hydrogen peroxide (mass concentration of hydrogen peroxide of 30%, Xilong Scientific Co., Ltd., brand: 1560010104299), and is subjected to ultrasonic treatment in a 60°C water bath for 2 h to obtain activated graphite with a surface rich in sulfonic acid groups (-SO3H), which is then washed with distilled water until neutral and vacuum dried.

[0106] (2) In-situ synthesis of nitrogen-doped carbon / metal phosphide heterojunction: The activated graphite is immersed in 20 mL of 0.5 mol / L NH4FePO4 solution (Shanghai Aladdin Bio-Chem Technology Co., Ltd., brand: F188971) in a vacuum environment and left to stand for 4 h. Then, stirring is performed at 600 rpm / min at 50°C until the solvent of the NH4FePO4 solution is completely evaporated, and the third precursor is formed by grinding and crushing under an Ar / H2 (95% / 5%) atmosphere and annealing at 800°C for 4 h.

[0107] (3) Al2O3coating: The third precursor material was transferred to the ALD reaction chamber, and the temperature was set to 80°C. The cycle parameters were set as TMA pulse 0.1 s, nitrogen purge 10 s, H2O pulse 0.05 s, and nitrogen purge 10 s. Six cycles were deposited to obtain an Al2O3 layer with a thickness of 1 nm. The negative electrode material of the nitrogen-doped carbon / metal phosphide / oxide gradient heterojunction interface layer was prepared.

[0108] Comparative Example 4

[0109] (1) Graphite pretreatment: 10 g of artificial graphite raw material (D50 of 12.5 pm, Zhongke Xingcheng Graphite Co., Ltd., brand: RPG215) was mixed with 150 ml of concentrated sulfuric acid (mass concentration of 98%, Shanghai Aladdin Biochem Technology Co., Ltd., brand: S433910) and 50 ml of hydrogen peroxide (mass concentration of hydrogen peroxide of 30%, Xilong Scientific Co., Ltd., brand: 1560010104299), and was treated by ultrasonic treatment at 60°C for 2 h in a water bath to obtain activated graphite with a surface rich in sulfonic acid groups (-SO3H). After washing to neutral with distilled water, the activated graphite was vacuum dried.

[0110] (2) In-situ synthesis of nitrogen-doped carbon / metal phosphide heterojunction: The activated graphite was dispersed in 200 ml of Tris buffer solution with pH = 8.5, and 3 g of polydopamine (mass ratio to graphite of 0.3:1, weight average molecular weight of 70,000 Da, Shanghai Aladdin Biochem Technology Co., Ltd., brand: D103111) was added. The mixture was stirred at room temperature for 12 h, and then was centrifuged and dried to form a first precursor with a uniform polydopamine coating layer. The dried material was annealed at 800°C for 4 h in an Ar / H2 (95% / 5%) atmosphere to form a third precursor.

[0111] (3) Al2O3coating: The third precursor material was transferred to the ALD reaction chamber, and the temperature was set to 80°C. The cycle parameters were set as TMA pulse 0.1 s, nitrogen purge 10 s, H2O pulse 0.05 s, and nitrogen purge 10 s. Six cycles were deposited to obtain an Al2O3 layer with a thickness of 1 nm. The negative electrode material of the nitrogen-doped carbon / metal phosphide / oxide gradient heterojunction interface layer was prepared.

[0112] Preparation of the negative electrode tab:

[0113] The negative electrode active material, conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) prepared in the above examples and comparative examples were uniformly mixed in a mass ratio of 8:1:1, and N-methyl pyrrolidone was added to prepare a negative electrode slurry, which was then coated on the surface of a negative electrode current collector copper foil (thickness 8 pm) and vacuum dried at 80 °C for 12 h to form a negative electrode active material layer. Finally, the negative electrode sheet (thickness 80 pm, diameter 12 mm) was obtained through rolling and punching.

[0114] Preparation of lithium ion batteries:

[0115] Li pieces (diameter 14 mm) as the counter electrode and the above negative electrode sheet were assembled into CR2032 type button cells in a glove box with water oxygen content less than 0.01 ppm. The electrolyte used was a mixture of 1 M LiPF6and equal volume ratio of ethylene carbonate (EC) and dimethyl carbonate (DMC), with 3% vinylene carbonate (VC) added as an additive.

[0116] The negative electrode materials, negative electrode sheets, and lithium ion batteries prepared in each example and comparative example were tested for performance according to the following method, and the test results are shown in Table 1 and Table 2 below.

[0117] Thickness of nitrogen-doped carbon layer: The negative electrode material powder was dispersed in an ethanol solution, and after uniform dispersion, the dispersion liquid was dropped onto a copper mesh with a micro-grid. After drying, the material was tested using a JEM-2100 & X-Max80 type TEM instrument. In the test process, the entire carrier mesh was first quickly scanned at low magnification to find the target area, and then the thin area of the target area was moved to the center of the optical axis for accurate focusing. The TEM high magnification mode (10 nm, 5 nm) was switched, the condenser diaphragm and beam deflector were adjusted to center and uniform the beam spot on the sample, and the sample was confirmed to be stable under electron beam irradiation for image acquisition. In the high-resolution image, the amorphous region was the carbon layer. Rapid Fourier transform of the collected HR-TEM image can measure the interplanar spacing and determine the crystal type.

[0118] Mass fraction of nitrogen element: tested using an elemental analyzer (EA). The specific test method was as follows: 20 mg of the negative electrode material sample was placed in a tin foil boat and placed in a high-temperature combustion tube. After being fully burned (1000 °C) for 5 min in a pure oxygen atmosphere, the nitrogen in the sample was converted into nitrogen oxide (NO x The mixed gas produced by combustion first passed through a drying device to remove water, and then entered a reduction furnace (filled with copper chips as a reducing agent, temperature about 600 °C). NO xUnder the reduction of copper, it is converted into nitrogen gas. The separated N2 enters the thermal conductivity detector (TCD). The TCD generates an electrical signal proportional to the N2 concentration by measuring the difference in the thermal conductivity of the gas. The instrument calculates the nitrogen content in the sample by comparing the signal with that of a nitrogen standard sample with a known concentration. The instrument uses an acetanilide standard sample (containing 10.36% N) to correct for system error.

[0119] Average particle size of metal phosphide particles: The negative electrode material powder was dispersed in an ethanol solution. After uniform dispersion, the dispersion was dropped onto a copper grid with a microgrid and dried. Then, the material was tested using a JEM-2100 & X-Max80 TEM instrument. During the test, the entire grid was quickly scanned to find the target area. The target area was then magnified appropriately, and the sample height (Z-Height) was adjusted to the eucentric height (standard height) so that the sample was at the center of the objective lens focal plane. The sample movement was minimized when tilting the lens. An image was acquired, and the particle size of FeP was determined from the scale on the image.

[0120] Mass fraction of metal phosphide particles: Inductively coupled plasma (ICP) was used for testing. The specific method was as follows: 50 mg of the negative electrode material sample was added to 5 mL of aqua regia (HNO3:HCl = 1:3) and microwave digested (200℃, 30 min) to dissolve the metal phosphide particles doped in the graphite. The digested mixture was then diluted to 100 mL with ultrapure water and vacuum filtered through a 0.22 μm filter membrane. The filtrate was then subjected to ICP detection. Analytical line: For example, Fe 238.204 nm, quantified using the standard curve method (R...). 2 >0.999), the concentration C of metal ions in 100 ml of metal phosphide was measured. M The mass fraction of metal phosphide in the entire negative electrode material can then be calculated. The formula is: wt% metal phosphide = (C...) M *V*10 -3 ) / M M *M MP / M 样品 *100%, of which C M V is the metal ion concentration of the metal phosphide (μg / mL), V is the volume (mL), and M is the molar mass (g / mol), where M M M is the molar mass of the metal in the metal phosphide, where M MP M is the molar mass of the metal phosphide. 样品 The sample mass is in grams (g).

[0121] Thickness of metal oxide layer: The negative electrode material powder was dispersed in an ethanol solution, and after uniform dispersion, the dispersion liquid was dropped on a copper mesh with micro-grid, and dried. Then the material was tested using a JEM-2100 & X-Max80 type TEM instrument, and the test process was first to quickly scan the entire carrier mesh at low magnification, and to find the target ultra-thin area. The electron beam was accurately aligned with the electromagnetic lens system, the aberration was eliminated, the resolution was optimized, the condenser diaphragm and beam deflector were adjusted, the beam spot was centered and uniform on the sample, the objective lens diaphragm was removed or minimized, the TEM was switched to high magnification mode (2 nm), the sample was confirmed to be stable under electron beam irradiation, and image acquisition was performed. The collected HR-TEM image was subjected to fast Fourier transform to measure the interplanar spacing, and the crystal face type was determined by comparing with the standard card of Al2O3.

[0122] Particle size of negative electrode material: The laser particle size analyzer was used for testing, and the specific testing method was as follows: 1 g of negative electrode material powder was dispersed in 20 ml of deionized water, stirred for 5 min, and the dispersed suspension was slowly poured into the sample cell of the instrument, ensuring that the liquid covered the light path. The obscuration rate was observed through the test software, and if the concentration was too high, the dispersion medium needed to be diluted, and if it was too low, the sample needed to be supplemented to ensure stable scattering signal. The instrument automatically collected the scattering light signal, calculated the particle size distribution, and repeated the measurement of the same sample three times to take the average value (to reduce accidental errors). After the test was completed, the test software automatically generated the particle size distribution curve and the particle size characteristic value D50.

[0123] Electrical conductivity: The membrane resistance meter was used, and the negative electrode sheet to be tested was cut into a rectangular size of about 5 cm x 10 cm, placed on the sample table, and the test pressure (5 MPa) and pressure holding time (20 s) were set on the membrane resistance instrument software. Start testing, and read the electrical conductivity through the software.

[0124] Specific surface area: The negative electrode material was placed in the specific surface area instrument sample chamber and vacuum dried (200°C) for 4 h. Under low temperature (liquid nitrogen 77 K or liquid argon 87 K), inert gas (N2, Ar, Kr) was introduced into the sample chamber, and by measuring the gas adsorption equilibrium pressure and adsorption amount, the adsorption-desorption isotherm was drawn, and the specific surface area was calculated by the BET equation through the specific surface area instrument machine.

[0125] High rate cycle performance test: The lithium ion batteries assembled with the negative electrode materials of the examples and the comparative examples were tested at 0.1C, 1C and 4C constant current charge and discharge, respectively, with a voltage range of 0.005-2V and a test temperature of 25°C. The high and low capacities and the capacity retention rate after 1000 cycles at 1C and 4C rates were compared.

[0126] Table 1

[0127]

[0128] Table 2

[0129]

[0130]

[0131] It can be seen from the performance test and electrochemical performance test results of the negative electrode material, negative electrode sheet and lithium ion battery that the negative electrode material prepared in Examples 1-7 contains a nitrogen-doped carbon layer and a metal oxide layer, wherein the nitrogen-doped carbon layer contains metal phosphide particles, has a higher initial efficiency than Comparative Examples 1-4 which do not have the above structure, and has a higher capacity and capacity retention rate at different charge and discharge rates.

[0132] Specifically, the negative electrode materials prepared in Examples 1-3 contain FeP, CoP and MnP particles, respectively. It can be seen from the electrochemical performance test results in Table 2 that the negative electrode materials containing metal phosphide particles formed from different types of phosphorus sources all have a higher initial efficiency, capacity and capacity retention rate. In sharp contrast to Comparative Example 4, the preparation method of the negative electrode material of Comparative Example 4 is the same as that of Example 1 except that no phosphorus source is added to form metal phosphide, but the conductivity of the negative electrode material prepared in Comparative Example 4 is significantly lower, and the initial efficiency, capacity and capacity retention rate in the electrochemical performance test are also significantly lower than those of Example 1, especially the capacity retention rate at high rate. It can be seen that the nitrogen-doped carbon layer containing metal phosphide provided in the negative electrode material of the present application has a significant effect on improving the conductivity, initial efficiency, capacity and capacity retention rate of the negative electrode material.

[0133] Examples 4 and 5 differ from Example 1 in that the proportion of carbon source added is different. It can be seen from the test results in Table 1 that the thickness of the carbon layer and the content of nitrogen element of the prepared negative electrode material also change accordingly. Among them, the proportion of carbon source added in Example 4 is low, which makes the thickness of the nitrogen-doped carbon layer low and the content of nitrogen element low, and the conductivity and specific surface area of the negative electrode material decrease, and the initial efficiency, capacity and capacity retention rate in the electrochemical performance test also decrease; the proportion of carbon source added in Example 5 is high, and accordingly the thickness of the nitrogen-doped carbon layer is high and the content of nitrogen element is high. Although the conductivity increases slightly, the electrochemical performance such as initial efficiency, capacity and capacity retention rate decreases significantly. It can be seen that the thickness of the nitrogen-doped carbon layer and the content of nitrogen element in the negative electrode material have a significant effect on the electrochemical performance of the battery prepared therefrom, and too high or too low is not conducive to the improvement of the electrochemical performance.

[0134] Embodiments 6 and 7 differ from Embodiment 1 only in that the concentration of the phosphorus source is different, and the particle size and content of the metal phosphide particles in the prepared negative electrode material are different. Among them, the concentration of the phosphorus source in Embodiment 6 is low, and the particle size and content of the metal phosphide particles in the prepared negative electrode material are low. The concentration of the phosphorus source in Embodiment 7 is high, and the particle size and content of the metal phosphide particles in the prepared negative electrode material are high. Moreover, the electrical conductivity of the negative electrode materials of Embodiments 6 and 7 decreases. As can be seen from the electrochemical performance test results in Table 2, compared with Embodiment 1, the initial efficiency, capacity and capacity retention of Embodiments 6 and 7 all decrease to some extent. It can be seen that the particle size and content of the metal phosphide particles in the negative electrode material have a significant influence on its electrochemical performance, and too high or too low is not conducive to the improvement of its electrochemical performance.

[0135] Further, Comparative Example 1 tests the physicochemical properties and electrochemical properties of the untreated artificial graphite as the raw material of Embodiment 1 directly as a negative electrode material. It can be seen that the performance of the negative electrode material prepared in the embodiments of the application is significantly improved.

[0136] The negative electrode material prepared in Comparative Example 2 is not coated with aluminum oxide, so that the negative electrode material is easy to generate organic SEI, and the probability of side reactions of the negative electrode material after contacting with the electrolyte increases, so that the initial efficiency, capacity and capacity retention of the negative electrode material are significantly reduced, and the performance under high-speed charging and discharging is particularly significant.

[0137] The negative electrode material prepared in Comparative Example 3 is doped with metal phosphide, but does not have a nitrogen-doped carbon layer, so that the electrical conductivity is low, and the electrochemical properties such as initial efficiency, capacity and capacity retention are also poor. In combination with Comparative Example 4, it can be seen that when the coating layer includes a nitrogen-doped carbon layer containing metal phosphide particles, the metal oxide in the outermost layer can play a synergistic effect, so that the negative electrode material has excellent electrochemical properties.

[0138] The above only describes the preferred embodiments of the present application and is not intended to limit the present application. For those skilled in the art, the present application can have various modifications and changes. Any modification, equivalent replacement, improvement, etc. made within the spirit and principles of the present application shall be included in the protection scope of the present application.

Claims

1. A negative electrode material, characterized in that, include: The core is made of graphite, and the coating layer includes a nitrogen-doped carbon layer and a metal oxide layer arranged from the inside out. The nitrogen-doped carbon layer contains metal phosphide particles.

2. The negative electrode material according to claim 1, characterized in that, The thickness of the nitrogen-doped carbon layer is 20–40 nm; The carbon in the nitrogen-doped carbon layer is amorphous carbon; The nitrogen content in the negative electrode material is 3-6% by mass.

3. The negative electrode material according to claim 1, characterized in that, The average particle size of the metal phosphide particles is 6–10 nm. The metal phosphide includes any one or more of FeP, MnP, NiP, and CoP; The mass fraction of the metal phosphide particles in the negative electrode material is 0.5% to 2%.

4. The negative electrode material according to claim 1, characterized in that, The material of the metal oxide layer is aluminum oxide; The thickness of the metal oxide layer is 0.5–1.5 nm; The kernel has a particle size D50 of 10.08–15.1 μm.

5. The negative electrode material according to claim 1, characterized in that, The particle size D50 of the negative electrode material is 10.5–15.5 μm; The conductivity of the negative electrode material is 4.75–9.85 S / cm; The specific surface area of ​​the negative electrode material is 1.0–1.6 m². 2 / g.

6. A method for preparing a negative electrode material, characterized in that, include: Graphite, Tris buffer, and carbon source are mixed, and the liquid phase components are removed to obtain the first precursor, wherein the carbon source is an amine polymer; The first precursor is mixed with a phosphorus source solution to obtain a second precursor, and the second precursor is sintered to obtain a third precursor. A metal oxide layer is deposited on the surface of the third precursor to obtain the negative electrode material.

7. The preparation method according to claim 6, characterized in that, The graphite is activated graphite, and the surface of the activated graphite contains any one or more of sulfonic acid groups and phosphate groups; The steps for preparing the activated graphite include: mixing graphite raw material with an activation treatment solution, ultrasonic treatment, washing, and drying to obtain activated graphite; the activation treatment solution is a concentrated acid and hydrogen peroxide solution with a volume ratio of 2:1 to 4:

1. Preferably, the concentrated acid is concentrated sulfuric acid and / or concentrated phosphoric acid; Preferably, the temperature of the ultrasonic treatment is 50–70°C; Preferably, the ultrasonic treatment time is 1 to 3 hours.

8. The preparation method according to claim 6 or 7, characterized in that, The mass ratio of graphite to carbon source is 1: (0.2~0.4); The carbon source is selected from any one or more of polydopamine, polyethyleneimine, polyaniline, polyimide, dicyandiamide, and melamine resin; The weight-average molecular weight of the carbon source is 60,000 to 80,000 Da; The pH value of the Tris buffer solution is 8-9; The phosphorus source includes any one or more of NH4FePO4, NH4CoPO4·H2O, NH4MnPO4 and (NH4)2NiPO4; The concentration of the phosphorus source solution is 0.3–0.7 mol / L; The sintering process is carried out at a temperature of 700–900°C for 2–6 hours. The step of depositing a metal oxide layer on the surface of the third precursor includes: forming the metal oxide layer by depositing the third precursor through an outer atomic layer; preferably, the temperature of the outer atomic layer deposition is 70-90°C; preferably, the number of cycles of the outer atomic layer deposition is 5-10.

9. A negative electrode sheet, characterized in that, The negative electrode material comprising any one of claims 1 to 5 or the negative electrode material prepared by any one of claims 6 to 8.

10. A secondary battery, characterized in that, Includes the negative electrode sheet as described in claim 9.